APPLICATION OF CARBON DOTS FROM PAPAYA PEEL USING THE OVEN HEATING METHOD ON SPINACH PLANT GROWTH - Bunga Kusuma Putri; Rahmat Firman Septiyanto; Devi Ayu Nur'aini (Universitas Islam Sumatera Utara, 2026)
This study aims to synthesize carbon dots (C-dots) from papaya peel using the oven heating method and to examine their effect on spinach growth. The synthesis process involved carbonization, grinding, dissolution, and filtration to obtain a clear C-dots solution. UV light testing showed fluorescence emission, indicating the formation of carbon nanoparticles. C-dots were applied at concentrations of 0.5 g/L and 1 g/L, with distilled water as the control. Plant growth was observed through plant height for seven days. The results showed that C-dots improved plant growth compared to the control. The 1 g/L concentration was more effective in the early phase, while 0.5 g/L showed more stable effects in the later phase. These findings indicate the potential of C-dots as an environmentally friendly nanotechnology-based plant growth enhancer. Further research is recommended to explore other concentrations and growth parameters.